Academic Performance, Causal Attributions and Hope to Complete Studies among University Students - Muwonge, Charles Magoba; Ssenyonga, Joseph (PUB Scientific publication, 2015)
The study examined academic performance, causal attributions, and hope to complete university studies among undergraduate students of Mbarara University of Science and Technology (MUST). The sample comprised of 163 undergraduate students offering Bachelor of Science with Education in their first and second years of study. Data was collected using a questionnaire and focus group guide and was analyzed using SPSS – 16 and content analysis respectively. Most of the respondents were males (89%), government-sponsored (85.9%), aged between 18 – 22 years (78.5%), and having cumulative grade point averages (CGPA’s)/grade point averages(GPA’s) between 2.80 – 3.59 (49.1%). Students used internal attributions than external attributions in describing their academic performance. Students had significantly higher hope of completing their studies. There was a significant difference between year of study and internal attribution; with first year students having a higher internal attribution than second year students. There were significant relationships between students’ exact CGPA/GPA and age; exact CGPA/GPA and year of study and exact CGPA/GPA and sponsorship. Internal attribution was positively related to exact CGPA/GPA, hope to complete studies, pathways and agency. There is need for the university administration to use motivation techniques such as rewarding the best performers to instill a sense of competition among students as they strive to complete their studies. There is also need for attributional retraining among undergraduate students such that they can attribute their performances realistically which enhances their hope of completing studies.
Keywords: Agency, Attributions, Attributional Retraining, Cumulative Grade Point Averages, Pathways